A new species of Ajorama Otte, 1988 (Grylloidea, Landrevinae) from Mindanao, Philippines - Daguplo, Jiandy; Mondejar, Eddie; Tan, Ming Kai (Zootaxa, 2025)
Ajorama Otte, 1988 is a genus of Landrevinae subfamily endemic to the Philippines, with only two species described: A. balatukanis Otte, 1988 and A. siargaoensis (Tan, Gorochov, Baroga-Barbecho & Yap, 2019). In a recent fieldwork in Northern Mindanao, Philippines, a new species of Ajorama was discovered and is described here: Ajorama chelatoides sp. nov. It is most readily distinguished from other congeners by the male genitalia having a chelated (crab-like) pseudepiphallic lophi [posterolateral epiphallic lobe]. This represents the third described species of Ajorama. This genus remains endemic to Mindanao. A new locality record (Lanao del Norte, Iligan City) for Duolandrevus (Bejorama) gingoogus Otte, 1988, previously known from Mt. Pomalith, Misamis Oriental, is also reported.